Kajian Ritual Melaut dan Perubahannya pada Orang Bajo di Desa Tanjung Pinang Kecamatan Kusambi Kabupaten Muna - Hj. Wakuasa; La Ode Aris (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT This article discusses about the fishing ritual of Bajo ethnic in Tanjung Pinang village Kusambi district Muna regency. There are several things that become focus in this discussion that are the kinds of fishing ritual and its implementation of Bajo ethnic in the village of Tanjung Pinang. Then, analyze the changes of fishing ritual activities because the interaction with outside communities. The methods of data collection in this research are observation and interviews. The types of data in this study are primary and secondary data that analyzed by using qualitative data analysis. The results of this study indicated that the fishing ritual activities carried out when occur a decline of marine management and frequent accidents at sea. Aspects related to fishing ritual were religious, economic, psychological, democracy, environmental, social, and health aspects. The changes occurred in the form of the change of mindset and value in the community. The causes of the change was due to transmission constraints, the amalgamation, the high interaction with the outside communities, the inclusion of communication technology, electronic media and the influence of religious sects. Keywords: ritual, Bajo ethnic, change.